A Study and Analysis of the Process for Strengthening Academic Work Based on the Four Principles of Iddhipada among the Personnel of Phra Pariyattidhamma School, Wat Phraison Sakdaram (Royal Monastery), Lom Sak District, Phetchabun Province - Khosathommo(Comsas), Thanakorn; warakorn, PhraKhruSutakrun; Chuntawan, Udon (MCU Haripunchai Review, 2026)
This research aimed to 1) study the strengthening of academic performance 2) study the process model for strengthening academic performance according to the Four Bases and 3) propose guidelines for developing a process for strengthening academic performance according to the Four Bases of Iddhipada of personnel at Wat Phraisan Sakdaram Buddhist School (Royal Monastery), Lom Sak District, Phetchabun Province. This mixed-method research combined qualitative and quantitative research with a sample of 133 people. The research instruments included a social science software package. The methods used were frequency, percentage, mean, standard deviation, t-test, and one-way analysis of variance. Qualitative data were analyzed by descriptive inductive method. The research results revealed that: 1)Process of strengthening academic work According to the 4 Iddhipada principles of Phra Pariyattidhamma School, Wat Phraison Sakdaram. (Royal Monastery) Lom Sak District, Phetchabun Province It was found that the process of strengthening academic work according to the 4 Iddhipada principles was overall at a high level in every aspect. 2)Guidelines for studying and analyzing the process of strengthening academic work of the personnel of Phrapariyattidhamma School, Wat Phraison Sakdaram (Royal Monastery) Lom Sak District, Phetchabun Province 1) Curriculum: Educational institution administrators must have knowledge of science, practices, and technology. The curriculum is planned to be in line with the local context. There is systematic supervision and follow-up. 2) Learning management. Educational institutions should provide opportunities for subordinates to express their opinions regarding learning in various forms. 3)Results of the synthesis of the process of strengthening academic work. of the personnel of Phrapariyattidhamma School, Wat Phraison Sakdaram (Royal Monastery) Lom Sak District, Phetchabun Province The research results found that Overall, it is at a high level.